Liebe, Sexualität, Ehe: Unerledigte Themen der Theologie und der christlichen Kultur - Herms, Eilert (Zeitschrift für Theologie und Kirche, 1999)
This essay begins with a description of love between humans as a form of intimacy brought about by total pleasure. Based on this understanding of love and using it as his background, Eilert Herms interprets sexuality and marriage. It is the author's intention to make it clear in the first place that love, sexuality and marriage, being three different phenomena, are related to each other in different ways, and secondly that the relationships of these three phenomena among themselves can only be understood if love forms the all-encompassing horizon for this understanding. The author denies that love is based on physical attraction and that love and marriage can be treated as equivalents. This viewpoint concurs with that conveyed in the Bible, and makes it easier to deal with old disputes about sexual and marital ethics — regardless of the fact that some questions remain unanswered.